The effects of taste sensitivity and repeated taste exposure on children's intake and liking of turnip (Brassica rapa subsp. rapa); a bitter Brassica vegetable. (1st February 2021) - Mohd Nor, Nurfarhana Diana; Houston-Price, Carmel; Harvey, Kate; Methven, Lisa
Abstract: Low consumption of vegetables in children is a concern around the world, hence approaches aimed at increasing intake are highly relevant. Previous studies have shown that repeated taste exposure is an effective strategy to increase vegetable acceptance. However, few studies have examined the effect of repeated taste exposure on children varying in bitter taste sensitivity. This study investigated the influence of taste genotypes and phenotypes on the effects of repeated taste exposure to a Brassica vegetable. 172 preschool children aged 3–5 years were recruited into this study. Turnip was selected as the target vegetable and parents completed a questionnaire to ensure unfamiliarity. During the intervention, children were exposed to steamed-pureed turnip for 10 days (once/day). Intake and liking were measured before, during and after the intervention, and a follow-up was done 3 months post-intervention. Taste genotypes ( TAS2R38 and gustin ( CA6 ) genotypes) and taste phenotypes (PROP taster status and fungiform papillae density) were determined. There was a significant effect of exposure shown by significant increases in intake (p < 0.001) and liking (p = 0.008) post-intervention; however, there were no significant effects of taste genotypes or phenotypes on intake and liking. In summary, repeated taste exposure is confirmed to be a good strategy to increase vegetable acceptance in children, regardless of bitter taste sensitivity.